2022
DOI: 10.1029/2022gl100267
|View full text |Cite
|
Sign up to set email alerts
|

Future Changes in Active and Inactive Atlantic Hurricane Seasons in the Energy Exascale Earth System Model

Abstract: North Atlantic tropical cyclones (TCs) have considerable interannual variability, with La Niña and the positive phase of the Atlantic Meridional Mode (AMM) tending to drive active hurricane seasons, and El Niño and the negative AMM often driving inactive seasons. Here, we analyze how active and inactive Atlantic hurricane seasons may change in the future using the high resolution Energy Exascale Earth System Model (E3SM). We performed atmosphere‐only simulations forced by sea‐surface temperature patterns chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, E3SM projects a substantial increase in Atlantic hurricane season length by 41 days under mean climate change with neutral ENSO and AMM, and by 27 days under mean climate change paired with positive AMM and La Niña conditions. These future increases in Atlantic hurricane season length, taken together with substantial future increases projected in Atlantic TC number and intensity under both neutral AMM and ENSO and co‐occurring positive AMM and La Niña (Sena et al., 2022), indicate the potential for exacerbated Atlantic TC impacts in the future arising from more frequent and more intense TCs occurring over an extended hurricane season.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, E3SM projects a substantial increase in Atlantic hurricane season length by 41 days under mean climate change with neutral ENSO and AMM, and by 27 days under mean climate change paired with positive AMM and La Niña conditions. These future increases in Atlantic hurricane season length, taken together with substantial future increases projected in Atlantic TC number and intensity under both neutral AMM and ENSO and co‐occurring positive AMM and La Niña (Sena et al., 2022), indicate the potential for exacerbated Atlantic TC impacts in the future arising from more frequent and more intense TCs occurring over an extended hurricane season.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the historical observations, we analyzed 10‐member ensembles of TC‐permitting (∼0.38° resolution) atmosphere‐only E3SM simulations (Sena et al., 2022). The simulations include a (1) historical control, which represents the historical climate with seasonally varying SST (i.e., under neutral AMM and ENSO conditions), (2) historical “active” Atlantic hurricane season simulation, which is forced with the combined tropical Atlantic and Pacific SST patterns that tend to drive active Atlantic hurricane seasons (i.e., the positive phase of the AMM with La Niña), (3) historical “inactive” Atlantic hurricane season simulation, which is forced with the combined tropical Atlantic and Pacific SST patterns that tend to drive inactive Atlantic hurricane seasons (i.e., the negative phase of the AMM with El Niño), and (4–6) the same simulations as (1–3) but under future greenhouse gases, aerosol, and SST conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that seasonal TC activity in the North Atlantic is largely modulated by the difference in SSTAs between tropical Atlantic and Paci c basins 45 , a projected increase in the interannual variability of ENSO 51 and tropical North Atlantic SST 52 suggests an increase in the interannual variability of the future interbasin SST difference and hence North Atlantic TC activity. A recent work 53 used idealized SST-forced model experiments to investigate how extremes in seasonal TC activity may change due to the joint effects of ENSO and the Atlantic Meridional Mode and found that extremely active seasons becomes more common under anthropogenic effects, with greater TC number and a shift to stronger TCs. While these results are based on a single SST-forced model, without air-sea feedbacks, it highlights the importance of considering changes in the mean and interannual climate variability in uencing TC activity.…”
Section: Introductionmentioning
confidence: 99%